Study of the Role of Digital Literacy in Mitigating the Spread of Online Gambling as a Popular Cyber Crime in Indonesia - Septanto, Henri; Rusmawan, Uus; Yuliadi, Boy; Hidayatullah, Ari (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The spread of online gambling as a cyber crime has become a major problem in Indonesia. This type of cyber crime has a huge influence on various levels of society, both from a social and economic perspective. This research aims to examine the role of digital literacy in mitigating the spread of online gambling using a literature study approach. This study examines the definition and components of digital literacy and their impact in dealing with the risks associated with online gambling, which is now one of the most popular types of cyber crime in Indonesia. Through a literature review, this article explores existing theory and data on digital literacy and its effectiveness in increasing public awareness and protecting individuals from the risks associated with online gambling. The findings from this research indicate that digital literacy plays a key role in equipping society with the knowledge and skills necessary to recognize the dangers and impacts of online gambling, while also identifying several gaps in the literature that require further attention. The conclusion of this article emphasizes the importance of integrating digital literacy in mitigation strategies and offers recommendations for improving digital literacy programs to combat the spread of online gambling in Indonesia.